Fully Digital Audio Haptic Maps for Individuals with Blindness - Howard Kaplan; Anna Pyayt (Disabilities, 2024)
Tactile maps designed for individuals with blindness can greatly improve their mobility, safety and access to new locations. While 3D-printed maps have already been demonstrated to be a powerful tool for delivering spatial information, they might not always be available. Alternatively, a combination of audio and haptic information can be used to efficiently encode 2D maps. In this paper, we discuss the development and user-testing of a novel audio-haptic map creator application. Maps created using this application can provide people with blindness with a tool for understanding the navigational routes and layouts of spaces before physically visiting the site. Thirteen people with blindness tested various components of the virtual map application, such as audio, haptic feedback and navigation controls. Participants’ data and feedback were collected and analyzed to determine the effectiveness of the virtual maps as it relates to this user group’s readability and usability. The study showed that it was easy to use and that it efficiently delivered information about travel routes and landmarks that the participants could successfully understand.